Argumentation Structure of Retorts in Old Arabic Prose - Almadani, Ali Kadhim Ali (International Journal of Psychosocial Rehabilitation, 2020)
Retorts is an Arabic prosaic art that received an interest and attention during 9th century. The term is defined and several books were written about it, and this interest contributes to survive many examples of the art since it is an oral art. The researcher attempts to investigate the argumentative nature of this art, which is different from all other oral arts that depend on the question- answer dialogue. The researcher finds that it is a unique pattern in which the responder does not allow the dialogue to continue or use arguments. But the responder attempts to conclude the dialogue, and silence the questioner who has a desire to embarrass the official or make fun of him/ her. It is the responder’s reaction, then the responder also has the same intention to embarrass and make fun of the questioner. The responder has used rhetorical and pragmatic styles that the researcher refers to in this study.